Introduction to neglected tropical diseases - Molyneux, CMG, David (Henry Stewart Talks, 2019)
Neglected Tropical Diseases (NTDs), Global burden of NTDs, NTDs and the health system, NTDs and innovation, The socio-economical impact of NTDs, Role and importance of effective partnerships and alliances, Cost effectiveness of interventions and innovations, Examples of recent achievements and successes, Current challenges in NTD management